2010
DOI: 10.1111/j.1468-1331.2009.02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Periictal heart rate variability analysis suggests long‐term postictal autonomic disturbance in epilepsy

Abstract: We found decreased HRV immediately after the seizures, which lasted at least 5-6 h postictally, indicating a long-term postictal disturbance of the autonomous nervous system. GTCS were accompanied by a more decreased HRV than other seizures. Our results may have relevance in explaining pathomechanism of SUDEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 26 publications
4
51
0
Order By: Relevance
“…This postictal synchronization was more pronounced in the left-focus group. Severe postictal disturbances (dysregulations) of the ANS over a time range of 5-6 h are described by Toth et al [37] (HRV analysis). Therefore, it is not surprising that we found stronger synchronizations in both groups in comparison to those of the preictal period.…”
Section: The Influence Of the Focus Sidementioning
confidence: 94%
“…This postictal synchronization was more pronounced in the left-focus group. Severe postictal disturbances (dysregulations) of the ANS over a time range of 5-6 h are described by Toth et al [37] (HRV analysis). Therefore, it is not surprising that we found stronger synchronizations in both groups in comparison to those of the preictal period.…”
Section: The Influence Of the Focus Sidementioning
confidence: 94%
“…In our previous study we found that shortterm HRV decrease after epileptic seizures [51]. Following our experience with HRV, we tried to apply it to similar conditions, such as somatic pain stimulation.…”
Section: Introductionmentioning
confidence: 98%
“…Authors could not determine a clear-cut ECG abnormality that may be considered as a predictor for SUDEP. However, in other studies, authors observed an elevation of heart rate immediately after seizures, which were maintained for 5-6 hours postically, indicating a long-term postictal disturbance of the autonomous nervous system, suggesting that seizures may cause prolonged heart dysfunction (Toth et al, 2010;Pinto et al, 2011). Although seizure-induced asystole is a rare complication and tended to follow a period of apnea, epilepsy can be correlated to severe bradycardia or asystole (Walker & Fisch, 1997).…”
Section: Cardiac Mechanismsmentioning
confidence: 92%